Chemokine-targeted therapies: An opportunity to remodel immune profiles in gastro-oesophageal tumours. (28th November 2021) - O'Donovan, Cillian; Davern, Maria; Donlon, Noel E.; Lysaght, Joanne; Conroy, Melissa J.
Abstract: Immunotherapies are transforming outcomes for many cancer patients and are quickly becoming the fourth pillar of cancer therapy. However, their efficacy of only ∼25% in gastro-oesophageal cancer has been disappointing. This is attributed to factors such as insufficient patient stratification and the pro-tumourigenic immune landscape of gastro-oesophageal tumours. The chemokine profiles of solid tumours and the availability of effector immune cells greatly influence the immune infiltrate, producing 'cold' or 'immune-excluded' tumours in which immunotherapies are unable to reinvigorate the immune response. Other biological functions for chemokines have emerged, such as promoting cell survival, polarising T cell responses, and supporting several hallmarks of cancer. Therefore, chemokine networks may be exploited with therapeutic intent to mobilise and polarise anti-tumour immune cells, with further utility as combination treatments to augment the efficacy of current cancer immunotherapies. Few studies have demonstrated the clinical benefit of chemokine-targeted therapies as monotherapies, and this review proposes their consideration as combination treatments. Herein, we explore the anti-tumour and pro-tumour implications of chemokine signalling in gastro-oesophageal cancer and discuss their value as prognostic and predictive biomarkers in response to treatment. Highlights: The chemokine profiles of solid tumours greatly influence the immune infiltrate. Chemokines have been implicated as mediators of tumourigenesis and metastasis. Chemokine-targeted therapies offer a multipronged approach to tumour eradication. The chemokine system is severely dysregulated in gastro-oesophageal cancer. Chemokines can be exploited to impede tumour growth in gastro-oesophageal cancer.